c-Jun N-Terminal Kinases (JNKs) in Myocardial and Cerebral Ischemia/Reperfusion Injury - Shvedova M. V. Mariya Vitaljevna; Anfinogenova Ya. J. Yana Jonovna; Atochina E. N. Elena Nikolaevna; Shchepyotkin I. A. Igor Aleksandrovich; Atochin D. N. Dmitry Nikolaevich (2018, 2018)
Title screen